Zippered G-quadruplex/hemin DNAzyme: exceptional catalyst for universal bioanalytical applications. Issue 22 (8th December 2021) - Li, Jia; Wu, Haiping; Yan, Yurong; Yuan, Taixian; Shu, Yue; Gao, Xin; Zhang, Lu; Li, Siqiao; Ding, Shijia; Cheng, Wei
Abstract: G-quadruplex (G4)/hemin DNAzyme is promising horseradish peroxidase (HRP)-mimic candidate in the biological field. However, its relatively unsatisfactory catalytic capacity limits the potential applications. Inspired by nature protease, we conducted a proximity-enhanced cofactor assembly strategy (PECA) to form an exceptional HRP mimic, namely zippered G4/hemin DNAzyme (Z-G4/H). The hybridization of short oligonucleotides induced proximity assembly of the DNA-grafted hemin (DGH) with the complementary G4 sequences (cG4s), mimicking the tight configuration of protease cofactor and apoenzyme. The detailed investigations of catalytic efficiency and mechanism verified the higher activity, more rapid catalytic rate and high environmental tolerance of the Z-G4/H than the classical G4/hemin DNAzymes (C-G4/H). Furthermore, a proximity recognition transducer has been developed based on the PECA for sensitive detection of gene rearrangement and imaging human epidermal growth factor receptor 2 protein (HER2) dimerization on cell surfaces. Our studies demonstrate the high efficiency of Z-G4/H and its universal application potential in clinical diagnostics and biomolecule interaction research. It also may offer significant opportunities and inspiration for the engineering of the protease-free mimic enzyme.